2007
DOI: 10.1007/s12237-007-9000-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influence of the Needle Rush Juncus roemarianus on Saltmarsh Pore Water Geochemistry

Abstract: Previous studies have shown that saltmarsh macrophytes have a significant influence on sediment biogeochemistry, both through radial release of oxygen from roots and also via primary production and release of labile organic exudates from roots. To assess the seasonal influence of the needle rush, Juncus roemarianus, on saltmarsh sediment geochemistry, pore waters and sediments were collected from the upper 50 cm of two adjacent sites, one unvegetated and the other vegetated by Juncus roemarianus, in a Georgia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The processes included are solubilisation of chemically bound carbon and the decomposition of structurally bound carbon. Here there is no reference to the component of the carbon pool produced or removed by the plants, however, Koretsky & Miller (2008) report that total organic carbon is typically higher in un-vegetated sites. Jones et al (2017) also reported a release of DOC from FCWs, which they attributed to leaching from root exudates and soil organic matter.…”
Section: Phenolics and Docmentioning
confidence: 96%
“…The processes included are solubilisation of chemically bound carbon and the decomposition of structurally bound carbon. Here there is no reference to the component of the carbon pool produced or removed by the plants, however, Koretsky & Miller (2008) report that total organic carbon is typically higher in un-vegetated sites. Jones et al (2017) also reported a release of DOC from FCWs, which they attributed to leaching from root exudates and soil organic matter.…”
Section: Phenolics and Docmentioning
confidence: 96%
“…Decomposition of black needlerush occurs in standing senescent plants (Walker and Campbell, 2010) and decomposes more slowly than S. alterniflorus (Haines and Hanson, 1979). Koretsky and Miller (2008) reported that degradation of organic matter is coupled mostly with Fe 31 and sulfate reduction. Decomposition in the first month after plant death is attributed to leaching of water-soluble compounds followed by a weight loss of 60% to 70% in the next 7 months (McKee and Seneca, 1982).…”
Section: Detritus and Decompositionmentioning
confidence: 99%